Pendampingan Digital Marketing melalui Shopee Affiliate dalam Meningkatkan Ekonomi Desa Ngrogung - Ahmad Nur Mufti; Setia Dwi Ratnawati (Social Science Academic, 2025)
The purpose of this research is to understand how Shopee`s affiliate program uses a prediction system and what benefits it offers to users and sellers.Affiliate marketing is a type of partnership where businesses, groups, or individuals earn money when someone makes a purchase through their promotion.Shopee`s affiliate program is the company`s official program for website creators who want to increase their income by promoting Shopee products on social media. The first step was collecting data from several influential users of the Shopee affiliate program. However, because it's easy to use and offers many benefits, this approach might change how people spend their money.